2022
DOI: 10.1007/s12633-022-01777-6
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Analysis and Optimization of GAA Nanowire FET Towards Low Power and High Switching

Abstract: The main aim of this work is to study the effect of symmetric and asymmetric spacer length variations towards source and drain on n-channel SOI JL vertically stacked (VS) nanowire (NW) FET at 10 nm gate length (L G ). Spacer length is proved to be one of the stringent metrics in deciding device performance along with width, height and aspect ratio (AR). The physical variants in this work are symmetric spacer length (L SD ), source side spacer length (L S ) and drain side spacer length (L D ). The simulation re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, the I ON can still be modified to a higher level by using the gate stacking technique and this device can be used for low power circuit implementation. 8.2×10 9 70.37 39.5 GC-IG-NWTFET [36] 4.2×10 8 74 8 DMG-HD-VTFET [37] 2.6×10 11 18.1 -GAA Nanowire FET [38] 3.19×10 8 61.5 -Multi Bridge channel FET [39] 1.7×10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the I ON can still be modified to a higher level by using the gate stacking technique and this device can be used for low power circuit implementation. 8.2×10 9 70.37 39.5 GC-IG-NWTFET [36] 4.2×10 8 74 8 DMG-HD-VTFET [37] 2.6×10 11 18.1 -GAA Nanowire FET [38] 3.19×10 8 61.5 -Multi Bridge channel FET [39] 1.7×10…”
Section: Discussionmentioning
confidence: 99%
“…Here IIP3 & VIP3 of the proposed device are higher, and IMD3 is lower than the other devices [30][31][32] with the lower value of VIP2. Thus the proposed device Inner-Gated NWTFET [36], Dual Material Gate Heterogeneous Dielectric Vertical TFET [37], GAA Nanowire FET [38], Multi Bridge channel FET [39] and Nanosheet FET [40] are compared with proposed device Electrostatically doped Vertical Nanowire TFET & it is observed that E-VNWTFET is having better I ON /I OFF, Lower DIBL and better subthreshold slope than most of the devices.…”
Section: Characteristics Variation Of E-vnwtfet For Various Scaled Di...mentioning
confidence: 99%
“…The gain bandwidth product (GBW) is used to estimate the device efficacy in high frequency applications. 23 Mathematically GBW can be evaluated as: 26 GBW g C 20 6…”
Section: Figure 8b Depicts the Delay τmentioning
confidence: 99%
“…9,10 Researchers came up with the implementation of high-k gate stack to combat this problem. 11 Also, multiple device engineering such as Silicon on Insulator (SOI) technology, 12 2D channel materials, 13 Double gate (DG), 14 Trigate, 15 Fin-shaped field effect transistor (FinFET), 16 gate all around (GAA) FETs [17][18][19][20] are implemented. In the DG transistor, the gate is present at the top and down sides of the channel and improves the gate's electrostatic integrity and offers better short channel performance.…”
mentioning
confidence: 99%